1987
DOI: 10.1111/j.1365-2265.1987.tb00780.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of Basal Plasma Cortisol Assays in the Assessment of Pituitary‐adrenal Insufficiency

Abstract: A basal plasma cortisol value taken in a physically unstressed state in 68 patients with or without hypothalamic-pituitary-adrenocortical disease was compared with the maximal plasma cortisol concentration during an insulin tolerance test. There was a strong positive correlation between the values. Basal cortisol levels above 300 nmol/l (RIA method) almost excluded ACTH-cortisol insufficiency and those below 100 nmol/l strongly suggested dysfunction. A repeated basal cortisol estimation within a month was espe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
137
1
10

Year Published

1989
1989
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(155 citation statements)
references
References 9 publications
7
137
1
10
Order By: Relevance
“…According to the results of the preoperative ITTs which were performed on 55 patients in this study, we found that patients with basal serum cortisol levels between 165 and 496 nmol/l (6-18 mg/dl) required dynamic testing. The majority of previous studies determined the lower cut-off for basal cortisol as 100-110 nmol/l (3.6-4 mg/dl), but the upper cut-off was found to range between 300 and 494 nmol/l (10.8-17.9 mg/dl) (15)(16)(17)(18). In a metaanalysis of 12 studies, basal cortisol levels !5 mg/dl (138 nmol/l) were found to predict HPA insufficiency best, and values O13 mg/dl (365 nmol/l) predicted normal HPA function (19).…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of the preoperative ITTs which were performed on 55 patients in this study, we found that patients with basal serum cortisol levels between 165 and 496 nmol/l (6-18 mg/dl) required dynamic testing. The majority of previous studies determined the lower cut-off for basal cortisol as 100-110 nmol/l (3.6-4 mg/dl), but the upper cut-off was found to range between 300 and 494 nmol/l (10.8-17.9 mg/dl) (15)(16)(17)(18). In a metaanalysis of 12 studies, basal cortisol levels !5 mg/dl (138 nmol/l) were found to predict HPA insufficiency best, and values O13 mg/dl (365 nmol/l) predicted normal HPA function (19).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, a random serum cortisol of over 400 nmol/L at any time of the day makes adrenal insufficiency highly unlikely, 8 while a morning serum cortisol of less than 100 nmol/L strongly suggests adrenal failure. 13 In interpreting such results, one must consider the patient's current and prior steroid usage, as well as conditions affecting cortisol binding globulin, such as pregnancy or oral estrogen therapy, which can result in falsely reassuring cortisol concentrations.…”
Section: Investigating Adrenal Insufficiencymentioning
confidence: 99%
“…The magnitude of the stress response to major surgery in 20 adult subjects was established by Plumpton & Besser (1), who equated it to a peak cortisol response to the ITT of 550 nmol/l (20 mg/dl). More recently, this value has been revised downwards to 500 nmol/l (18 mg/dl) (9) and has been validated in healthy adults (10), correcting for the 20-30% positive bias associated with the older fluorometric assay (1). Extrapolation from adult data has resulted in many paediatric centres employing a reference range for peak cortisol responses to insulin-induced hypoglycaemia between 500 and 550 nmol/l for all children and adolescents regardless of age (1,2,10).…”
Section: Introductionmentioning
confidence: 99%